2021
DOI: 10.3390/mi12020206
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Advanced Properties of Electrowetting Displays

Abstract: Electrowetting display (EWD) has promising prospects in the electronic paper industry due to it having superior characteristics, such as the ability to provide a comfortable reading experience and quick response. However, in real applications, there are also problems related to dielectric deterioration, excess power consumption, optical instability and narrow color gamut etc. This paper reviewed the existing challenges and recent progress made in terms of improving the optical performance and reliability of EW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/jacs.2c13630. Materials and chemicals, preparation of the electrodes, electrowetting setup configuration, PTFE cell configuration, synthesis and NMR spectra ( 1 H, 13 C, 19 F, and 7 Li) of EMIM-TFSI, surface tension and mass density measurements, electrochemical measurements, calculation of capacitance from electrochemical impedance measurements, contact angle measurements, in situ Raman spectroscopy measurements, predicting the electrowetting response using the Y−L equation, contact angle variations upon deep intercalation/deintercalation in EMIM-TFSI, surface electrochemistry of LiClO 4(PC) in hexadecane, interfacial surface tension and work of adhesion at the liquid−liquid interface, dynamic measurements in the biphasic systems, electrowetting under AC in the biphasic systems, optical images of the droplets at selective potential biases for the systems under study, and electrowetting performance of selected biphasic systems reported in the literature (PDF) Changes in apparent contact angle during 200 wetting/ dewetting cycles for a 1 M LiClO 4(PC) droplet on HOPG in air (MP4) Changes in apparent contact angle at the EMIM-TFSI| HOPG interface in air upon application of a constant potential pulse for 200 s at +1.7 V with subsequent stepping to 0 V (MP4) Changes in apparent contact angle at the 20 m LiTFSI (aq) |HOPG interface in air upon application of a constant potential pulse for 200 s at +0.8 V with subsequent stepping to 0 V (MP4) Changes in apparent contact angle during 200 wetting/ dewetting cycles following the protocol described in the Experimental Section, for a 1 M LiClO 4(PC) droplet on HOPG in hexadecane (MP4) Changes in apparent contact angle during 200 wetting/ dewetting cycles following the protocol described in the Experimental Section, for a 20 m LiTFSI (aq) droplet on HOPG in hexadecane (MP4)…”
Section: * Sı Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/jacs.2c13630. Materials and chemicals, preparation of the electrodes, electrowetting setup configuration, PTFE cell configuration, synthesis and NMR spectra ( 1 H, 13 C, 19 F, and 7 Li) of EMIM-TFSI, surface tension and mass density measurements, electrochemical measurements, calculation of capacitance from electrochemical impedance measurements, contact angle measurements, in situ Raman spectroscopy measurements, predicting the electrowetting response using the Y−L equation, contact angle variations upon deep intercalation/deintercalation in EMIM-TFSI, surface electrochemistry of LiClO 4(PC) in hexadecane, interfacial surface tension and work of adhesion at the liquid−liquid interface, dynamic measurements in the biphasic systems, electrowetting under AC in the biphasic systems, optical images of the droplets at selective potential biases for the systems under study, and electrowetting performance of selected biphasic systems reported in the literature (PDF) Changes in apparent contact angle during 200 wetting/ dewetting cycles for a 1 M LiClO 4(PC) droplet on HOPG in air (MP4) Changes in apparent contact angle at the EMIM-TFSI| HOPG interface in air upon application of a constant potential pulse for 200 s at +1.7 V with subsequent stepping to 0 V (MP4) Changes in apparent contact angle at the 20 m LiTFSI (aq) |HOPG interface in air upon application of a constant potential pulse for 200 s at +0.8 V with subsequent stepping to 0 V (MP4) Changes in apparent contact angle during 200 wetting/ dewetting cycles following the protocol described in the Experimental Section, for a 1 M LiClO 4(PC) droplet on HOPG in hexadecane (MP4) Changes in apparent contact angle during 200 wetting/ dewetting cycles following the protocol described in the Experimental Section, for a 20 m LiTFSI (aq) droplet on HOPG in hexadecane (MP4)…”
Section: * Sı Supporting Informationmentioning
confidence: 99%
“…Wetting phenomena are ubiquitous, underpinning physicochemical processes occurring in both nature and artificial systems. Even their simple macroscopic observation can provide significant molecular insights into the properties of interfaces as well as those of the adjoining bulk phases. A number of diverse technologies, from electrochemical energy conversion, storage , and capacitive deionization (CDI) , to variable optics, displays, , and lab-on-a-chip systems, , are driven by wetting processes which occur under the application of an external electric field, a phenomenon referred to as electrowetting . Controlling wettability under these conditions is of paramount importance for product design, since any variations in wettability can have significant implications for the operation of the devices (such as lack of adhesion, , hysteresis, and loss of electrochemical activity ), resulting in performance decrease and/or failure.…”
Section: Introductionmentioning
confidence: 99%
“…By reducing the oil film thickness, the aperture can reach 80%. While narrow down the pixel size and pixel wall thickness, the resolution can reach 250ppi [31] .…”
Section: Colored Oil Dynamic Manipulationmentioning
confidence: 99%
“…Electrowetting is used in several applications, such as micro-drop generation, mixing and splitting [ 1 , 2 ], high-speed droplet actuation [ 3 , 4 ], chip cooling [ 5 ], drug release and clinical diagnosis [ 6 , 7 ], e-paper and electronic display [ 8 , 9 ], energy harvesting [ 10 ], solar indoor lighting [ 11 ], optics and beam steering [ 12 , 13 ]. In most electrowetting studies, the primary focus has been to observe the drop deformation and contact-angle change when the applied voltage is varied.…”
Section: Introductionmentioning
confidence: 99%